Exploring the role of oxidative stress and mitochondrial dysfunction in β-damascone-induced aneuploidy - Tsuneo Hashizume; Satoru Munakata; Tomohiro Takahashi; Taku Watanabe (Genes and Environment)
Abstract Background The rose ketone β-damascone (β-Dam) elicits positive results in the in vitro micronucleus (MN) assay using human lymphocytes, but shows negative outcomes in the Ames test and combined in vivo MN and comet assays. This has led to the interpretation that the in vitro MN result is a misleading positive result. Oxidative stress has been suggested as an indirect mode of action (MoA) for in vitro MN formation, with the α, β-unsaturated carbonyl moiety of the β-Dam chemical structure expected to cause misleading positive results through this MoA. In this study, we investigated the role of oxidative stress in β-Dam-induced in vitro MN formation by co-treatment with the antioxidant N-acetyl-l-cysteine (NAC), thereby highlighting a possible link between mitochondrial dysfunction and aneugenicity. Results β-Dam induced MN formation in both CHL/IU and BEAS-2B cells, with the response completely inhibited by co-treatment with NAC. Moreover, β-Dam induced oxidative stress-related reporter activity in the ToxTracker assay and increased reactive oxygen species levels, while decreasing glutathione levels, in BEAS-2B cells in the high-content analysis. All of these effects were suppressed by NAC co-treatment. These findings indicate that β-Dam elicits oxidative stress, which causes DNA damage and ultimately leads to MN induction. However, no significant DNA damage-related reporter activities were observed in the ToxTracker assay, nor was there an increased number of γH2AX foci in the high-content analysis. These data suggest that MN formation is not a DNA-reactive MoA. Considering recent reports of aneuploidy resulting from chromosome segregation defects caused by mitochondrial dysfunction, we investigated if β-Dam could cause such dysfunction. We observed that the mitochondrial membrane potential was dose-dependently impaired in BEAS-2B cells exposed to β-Dam. Conclusions These findings suggest that the oxidative stress induced by β-Dam exposure may be explained through an aneugenic MoA via mitochondrial dysfunction, thereby contributing to MN formation in mammalian cells.